(untitled) - Harrison, Graham (New York, 2005)
Bringing together leading scholars, the book investigates the ways in which development has become a significant consideration in International Political Economy. As such, it engages with a series of global encounters, between development studies, IPE and globalization: the state and global development; civil society networks and changing geographies of power and governance; global designs of regulatory change and more specific interests and agencies.
Keywords: International economic relations,Globalization,Economic development,Globalization; Congresses,Economic aspects,Congresses,Developing countries